(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: Русский язык служит важным средством коммуникации, обеспечивая эффективную передачу информации и взаимодействие людей в различных сферах. В данной статье мы анализируем его значение в межкультурном и деловом диалоге, а также в образовательном контексте. Особое внимание уделяется вопросу развития языковой компетенции, которая выступает ключевым фактором успешности коммуникации. Также рассматриваются актуальные вызовы, среди которых особое внимание уделяется влиянию цифровых технологий и искусственного интеллекта на языковые явления и коммуникативные практики. Abstract: The Russian language serves as an important means of communication, ensuring the effective transfer of information and interaction of people in various fields. In this article, we analyze its importance in intercultural and business dialogue, as well as in the educational context. Particular attention is paid to the development of linguistic competence, which is a key factor in the success of communication. Current challenges are also considered, among which special attention is paid to the influence of digital technologies and artificial intelligence on linguistic phenomena and communicative practices.